DESIGN OF AN OPEN-CIRCUIT WIND TUNNEL WITH PIV (PARTICLE IMAGE VELOCIMETRY) SYSTEM - Rendi, Rendi (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2024)
This study aims to design a wind tunnel. The designed wind tunnel is an open-circuit wind tunnel with a Particle Image Velocimetry (PIV) system. The wind tunnel has dimensions of 8 meters in length, 1.75 meters in width, and 1.75 meters in height, with a maximum speed of 30 m/s. The design results show that the head loss in the test section is 1.28 meters, the head loss in the contraction chamber is 0.52 meters, and the head loss in the diffuser is 0.49 meters. Therefore, the total head loss is 2.29 meters, requiring a blower power of 11.94 Hp